Methods for the Induction of Reproduction in a Tropical Species of Filamentous Ulva - Carl, Christina; de Nys, Rocky; Lawton, Rebecca J.; Paul, Nicholas A. (PLOS ONE, 2014)
The green seaweed Ulva is a major fouling organism but also an edible aquaculture product in Asia. This study quantified for the first time the effect of key factors on the reproduction of a tropical species of filamentous Ulva (Ulva sp. 3). The controlled timing of release of swarmers (motile reproductive bodies) was achieved when experiments were initiated in the early afternoon by exposing the thalli to a temperature shock (4°C) for 10 min and subsequently placing them into autoclaved filtered seawater under a 12 h light: 12 h dark photoperiod at 25°C. The release of swarmers then peaked two days after initiation. In contrast, segmentation, dehydration, salinity or time of initiation of experiments had no effect of any magnitude on reproduction. The released swarmers were predominantly biflagellate (95%), negatively phototactic and germinated without complementary gametes. This indicates that Ulva sp. 3 has a simple asexual life history dominated by biflagellate zoids.